Phase equilibria and geochronology of Ossa-Morena eclogites - Moita, Patricia (2010)
The mineralogical evolution of OMZ eclogites was modelled by calculated P-T pseudosection analysis for an appropriate bulk composition in the model system CNFMASH. OMZ eclogites having developed a clockwise P-T path that reached 16-18 kbar and 600-650 ºC, underwent isothermal decompression to 12-10 kbar before final cooling (< 550 ºC) to greenschist facies conditions. Sm/Nd and Ar/Ar radiometric data indicate that the OMZ eclogite facies metamorphism took place at ~370 Ma, being followed shortly afterwards by exhumation during (D1) nappe emplacement.